2006
DOI: 10.1111/j.1365-2389.2006.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Lime and cow slurry application temporarily increases organic phosphorus mobility in an acid soil

Abstract: Phosphorus loss from agricultural soils to water is recognized as a major contributor to eutrophication of surface water bodies. There is much evidence to suggest that liming, a common agricultural practice, may decrease the risk of P loss by decreasing P solubility. An unsaturated leaching column experiment, with treatments of control and two lime rates, was carried out to investigate the effects of liming on P mobility in a low-P acid Irish soil, which was sieved and then packed in columns. Phosphorus was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 50 publications
(66 reference statements)
2
21
2
1
Order By: Relevance
“…The ratio of N to K in DSW (1:1) compared to typical grassland requirements (2:1, at a stocking rate of 170 kg ha −1 organic N; Coulter et al 2002) may also result in excess K application. Excessive quantities of P and K in soils can result in P and K leaching (mainly through coarse, sandy, well drained soils) (Price, 2006;Murphy, 2007). Excessive K in soils can lead to elevated concentrations in grass that can pose a threat to livestock health, notably calcium deficiency (milk fever or hypocalcaemia) and magnesium deficiency (grass tetany or hypomagnesaemia) (Wang et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of N to K in DSW (1:1) compared to typical grassland requirements (2:1, at a stocking rate of 170 kg ha −1 organic N; Coulter et al 2002) may also result in excess K application. Excessive quantities of P and K in soils can result in P and K leaching (mainly through coarse, sandy, well drained soils) (Price, 2006;Murphy, 2007). Excessive K in soils can lead to elevated concentrations in grass that can pose a threat to livestock health, notably calcium deficiency (milk fever or hypocalcaemia) and magnesium deficiency (grass tetany or hypomagnesaemia) (Wang et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…P loss can also occur through drainage, however, with the most significant instances of downward movement of P through the soil profile being associated with excessive application of P in manure and fertiliser (Sims et al 1998;Murphy 2007), in particular, on soils with low P-retention properties and/or significant preferential f low pathways, for example cracking clay soils (Hart et al 2004).…”
Section: Measuring and Quantifying Phosphorus Transfer From Arable Somentioning
confidence: 99%
“…Until now, the majority of research in Ireland has focused on quantifying nutrient and, to a lesser extent, sediment losses from permanent grassland at laboratory- (Doody et al 2006;Murphy 2007;Murphy and Stevens 2010), plot/field- (Tunney et al 2007;Kurz et al 2000;Douglas et al 2007) and catchment-scales (Smith et al 1995;Scanlon et al 2004;Jordan et al 2005a;2005b;Smith et al 2005;Jordan et al 2007). Modelling of diffuse P loss from grassland catchments has also been undertaken by Jordan et al (2000), Daly et al (2002), Scanlon et al (2005) and Nasr et al (2007), with the aim of improving management strategies to minimise P loss.…”
Section: Research To Date On Sediment and P Lossmentioning
confidence: 99%
“…Whalen et al (2002) suggested that a distance B40 km from the source to the point of application makes it economical to substitute fresh cattle manure for lime in northern Alberta. Other studies under controlled laboratory (Naramabuye and Haynes 2006;Murphy 2007;Schefe et al 2008a) or greenhouse conditions (Hue 1992;Tang et al 2007;Schefe et al 2008b) have also demonstrated the liming effects of different manures on acid soils. While few studies have been conducted under field conditions, Eghball (1999) successfully demonstrated that cattle feedlot manure increased the pH of an acid soil in the central United States of America during a 4-yr field trial.…”
mentioning
confidence: 99%